A practical guide to outcome-focused philanthropy - Twersky, Fay; Grange, Lori (Hewlett Foundation, 2016)
Outcome-focused philanthropy is the Hewlett Foundation’s approach to h ow we practice strategic philanthropy. It guides how we do our work, f rom start to finish. We’ve been practicing strategic philanthropy for more than a decade—focusing on what problem or opportunity we’re tryin g to address, whether we’re achieving our outcomes and why (or why not ), and how…